Augmented Reality in Neurosurgery, State of Art and Future Projections. A Systematic Review - Cannizzaro, Delia; Zaed, Ismail; Safa, Adrian; Jelmoni, Alice J. M.; Composto, Antonio; Bisoglio, Andrea; Schmeizer, Kyra; Becker, Ana C.; Pizzi, Andrea; Cardia, Andrea; Servadei, Franco (Frontiers in Surgery, 2022)
Background: The use of augmented reality (AR) is growing in medical education, in particular, in radiology and surgery. AR has the potential to become a strategic component of neurosurgical training courses. In fact, over the years, there has been a progressive increase in the application of AR in the various fields of neurosurgery. In this study, the authors aim to define the diffusion of these augmented reality systems in recent years. This study describes future trends in augmented reality for neurosurgeons. Methods: A systematic review of the literature was conducted to identify research published from December 1st, 2011 to November 30th, 2021. Electronic databases (PubMed, PubMed Central, and Scopus) were screened. The methodological quality of studies and extracted data were assessed for “augmented reality” and “neurosurgery”. The data analysis focused on the geographical distribution, temporal evolution, and topic of augmented reality in neurosurgery. Results: A total of 198 studies have been included. The number of augmented reality applications in the neurosurgical field has increased during the last 10 years. The main topics on which it is mostly applied are spine surgery, neuronavigation, and education. The geographical distribution shows extensive use of augmented reality in the USA, Germany, China, and Canada. North America is the continent that uses augmented reality the most in the training and education of medical students, residents, and surgeons, besides giving the greatest research contribution in spine surgery, brain oncology, and surgical planning. AR is also extensively used in Asia for intraoperative navigation. Nevertheless, augmented reality is still far from reaching Africa and other countries with limited facilities, as no publications could be retrieved from our search. Conclusions: Augmented reality will allow the future generation of neurosurgeons to have a unified education plan across different neurosurgical centers. Such technologies in the near future could also improve neurosurgical training in countries with limited facilities that have specific targets in this program.